Collapse of a Public-Private Partnership in Uitenhage: A case study - M.D. Qolohle; N.B. Nyushman (South African Family Practice)
This paper examines the collapse of a public-private partnership (PPP) in the district of Uitenhage in 1999. Talks to revive the partnership are high on the agenda. It is therefore essential to examine the reasons for the collapse to avoid the pitfalls of the past and to ensure that a more sustainable and competent partnership is built for the future. The Eastern Cape is one of the most impoverished provinces of South Africa and can only benefit by better cooperation between the public and the private sectors.